The Role of Military-Patriotic and Other Events in the Field Prevention of Offenses - Shukhratjon Shakirov (Genius Publishing Group, 2022)
The article examines the role and significance of various measures, including those of a military-patriotic nature, in the field of crime prevention. At the same time, as the main object, the problems of the commission of offenses among young people, especially unorganized ones, as well as the issues of their reduction or prevention by various methods and methods are studied. The measures implemented in Uzbekistan in this area, primarily aimed at ensuring their employment and effective spending of time, and tasks for the future, are noted
Keywords: youth; minor; unorganized youth; reading; society